Mutually Exclusive Utilization of P(R) and P(RM) Promoters in Bacteriophage 434 O(R) - Xu, Jian (American Society for Microbiology, 2000)
Establishment and maintenance of a lysogen of the lambdoid bacteriophage 434 require that the 434 repressor both activate transcription from the P(RM) promoter and repress transcription from the divergent P(R) promoter. Several lines of evidence indicate that the 434 repressor activates initiation of P(RM) transcription by occupying a binding site adjacent to the P(RM) promoter and directly contacting RNA polymerase. The overlapping architecture of the P(RM) and P(R) promoters suggests that an RNA polymerase bound at P(R) may repress P(RM) transcription initiation. Hence, part of the stimulatory effect of the 434 repressor may be relief of interference between RNA polymerase binding to the P(RM) promoter and to the P(R) promoter. Consistent with this proposal, we show that the repressor cannot activate P(RM) transcription if RNA polymerase binds at P(R) prior to addition of the 434 repressor. However, unlike the findings with the related λ phage, formation of RNA polymerase promoter complexes at P(RM) and at P(R) apparently are mutually exclusive. We find that the RNA polymerase-mediated inhibition of repressor-stimulated P(RM) transcription requires the presence of an open complex at P(R). Taken together, these results indicate that establishment of an open complex at P(R) directly prevents formation of an RNA polymerase-P(RM) complex.